Sustainable Community Empowerment Approaches in the Mangrove Ecotourism Sector Through Creative Initiatives in Sei Nagalawan Village, Serdang Bedagai Regency, Indonesia: English - Sari, Anisah (CV. ARGA FARMA, 2024)
This study explores the potential and sustainable empowerment of the local community through the creative economy within the ecotourism area of Sei Nagalawan Village, Serdang Bedagai Regency. Utilizing a triangulation approach, the research gathers diverse perspectives, including insights from experts at the University of Sumatera Utara's Faculty of Forestry. The area features natural attractions such as mangroves, unique local products, and the shifting sands phenomenon. The Mangrove Conservation Group of Muara Baimbai plays a central role in fostering community empowerment. A SWOT analysis identifies key factors influencing development, including institutional support, limited government assistance, and the underutilization of technology in marketing. The findings demonstrate that ecotourism contributes positively to the local economy and community welfare while highlighting existing challenges. This research emphasizes the importance of sustainable strategies for ecotourism management, such as utilizing technology, expanding partnership networks, and enhancing human resource capabilities. The study concludes by stressing the need for increased government support, effective technology use, and a holistic approach to environmental conservation and community empowerment for the sustainable development of the ecotourism sector.